Analysis of the design parameters of multi-reference station RTK GPS networks - El-Mowafy, Ahmed (American Congress on Surveying and Mapping, 2005)
In this study, the main design parameters of multi-reference station RTKGPS networks have been analyzed, and their impact on the achieved positioning performance and phase ambiguity resolution is discussed. The main parameters considered are: the distance separating reference stations, network configuration, communication between the computing center and the user, and network algorithm. A number of tests have been conducted in a case study utilizing the Dubai Virtual Reference Network System (DVRS) in the United Arab Emirates. First, the real-time performance of the existing network was assessed. Next, the performance of the network was evaluated in a post-mission processing after making changes to its design, addressing the above parameters, by adding data from three auxiliary reference stations. Different network configurations were examined, consisting of variable combinations of the DVRS and the auxiliary stations. In addition, positioning results of two network algorithms (FKP/VRS and the Multiref methods) were compared. Finally, recommendations concerning the selection of baseline lengths, network architecture and station redundancy have been given.